2020
DOI: 10.1016/j.polymdegradstab.2020.109368
|View full text |Cite
|
Sign up to set email alerts
|

PBT plasticity loss induced by oxidative and hydrolysis ageing

Abstract: This paper reports the study of embrittlement of PBT submitted either to thermal or hydrolytic ageing. All changes were followed up by tensile tests, rheometry in molten state and gel permeation chromatography for molar mass changes, SAXS and DSC experiments for crystallinity changes. Both kind of ageing were shown to induce predominant chain scissions with moderate crystallinity increase, in great part due to annealing. The combination of all results were used to establish a M w -χ c embrittlement window help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…The residence time in the case of injection, or number of cycles in the case of extrusion [9] also induce changes in mechanical properties. It was actually previously shown that PBT becomes brittle when its molar mass becomes lower than a critical value (M' wc ) which depends on crystallinity [10]. Nevertheless, this critical value M' wc seems close to the (initial) molar mass value corresponding to common PBT grades for injection purposes [10] .…”
Section: Introductionmentioning
confidence: 66%
“…The residence time in the case of injection, or number of cycles in the case of extrusion [9] also induce changes in mechanical properties. It was actually previously shown that PBT becomes brittle when its molar mass becomes lower than a critical value (M' wc ) which depends on crystallinity [10]. Nevertheless, this critical value M' wc seems close to the (initial) molar mass value corresponding to common PBT grades for injection purposes [10] .…”
Section: Introductionmentioning
confidence: 66%
“…The experimental results, as well as their statistical processing, have shown that a connection radius between the walls of the parts that is as large as possible can cause a reduction in certain tendencies to crack the material. In addition, a correlation of the values of the three analyzed parameters (R, K, and α) can determine an increase in the lifespan of the parts [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 injection grades of poly(butylene terephthalate) were used in this study (detailed in Table 1 ). They were processed into about 150 to 200 μm thick films with a GIBITRE compacting press (200 bar) at 230 °C with an approximately 1min30 cycle (this temperature was chosen low enough to limit thermal degradation [4]).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to any ageing, tensile tests were performed on the three materials PBT1, PBT2 and PBT3. These tests were not conducted on the colored PBTs because their initial weight molar mass ( Table 1 ) were either lower than the M' wc previously established [4] or in the transition area resulting in brittle materials.…”
Section: Mechanical Properties Changesmentioning
confidence: 99%
See 1 more Smart Citation